Hybridization of fly ash – Moringa based composite for coagulation and disinfection of raw water - Mpho E. Tsie; Freeman Ntuli; Tumeletso Lekgoba; Vepika Kandjou (Next Materials)
This research study was conducted with the aim of investigating the effectiveness of using a Coal Fly Ash – Moringa oleifera based composite (CFA-MO) as a coagulant and a bacterial disinfectant in raw water treatment. From the bacterial quality control tests and jar test experiments, the best ratio of CFA to MO that sufficiently met the allowable disinfection and coagulation standards ascribed by the World Health Organisation was 1:2 at a total composite mass of 0.4 g/L. The ratio gave a disinfection bacterial removal rate of 100 % and coagulation reduction to less than 5 NTU translating to 96 % which qualifies it to be a good disinfectant and coagulant. The coagulation and disinfection processes were predominantly governed by second order and first order models respectively. A study on the critical coagulation rate constant as an evaluating parameter found the critical rate constants for low, medium, and high turbid water to be highest at k2 of 0.018, 0.009, 0.016 NTU−1. min−1 respectively. The mechanism that best describes CFA-MO coagulation was electrostatic destabilization where the highly negative colloidal suspensions are destabilized by the strongly charged aluminium metal ions present in CFA-MO. The Chick-Watson model was utilized for disinfection kinetics, and the log survival curve followed a lag or shoulder effect signifying that the microbes present in raw water initially react with the disinfectant thereby reducing the effectiveness of the disinfectant overtime. The study adds to waste valorisation and sustainability as waste materials and natural resources were used to coagulate and disinfect raw water.